Mass customization as a business model Business plan for online furniture company - Žák, Martin; Lukeš, Martin, 1976-; Mareš, Jan, 1986-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2015)
The goal of this thesis is to write a business plan for a mass customized online furniture company operating on Czech and Swiss market, analyse the potential and feasibility of this business idea and calculate the financial estimates of the business. The first part of the thesis describes the theoretical background and is focused on four main parts. First part tackles the topic of Canvas, Lean Canvas and lean startup approach. Second describes parts of the business plan. Thirdly the theoretical part focuses on the online customer experience and finally mass customization concept is discussed. The second part of this thesis is a practical business plan for an innovative online furniture company. The business model is built on the mass customization concept and targets Switzerland and Czech Republic. The goal of this part is to verify the business model by conducting a proper customer survey, analyse the market potential, develop the company strategy and asses its feasibility based on the financial model.
Vedoucí práce: Martin Lukeš
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses